2014
DOI: 10.1080/15374416.2014.886254
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Externalizing and Internalizing Behavior in Kindergarten: Examining the Buffering Role of Early Social Support

Abstract: Objective This study tested an ecological model predicting children’s behavior problems in kindergarten from risk and protective factors (parent psychological distress, parenting behavior, and social support) during early childhood. Method Study participants were 1161 socio-demographically diverse mother-child pairs who participated in a longitudinal birth cohort study. The predictor variables were collected at two separate time points and based on parent reports; children were an average of two years old at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 53 publications
(50 reference statements)
2
31
2
5
Order By: Relevance
“…Most longitudinal studies monitored young children; among these studies, five focused on the behavior of children from 6 to 7.5 years old (Anhalt, Telzrow, & Brown, 2007;Ashman, Dawson, & Panagiotides, 2008;Barker, Copeland, Maughan, Jaffee, & Uher, 2012;Campbell, Matestic, von Stauffenberg, Mohan, & Kirchner, 2007;Heberle, Krill, Briggs-Gowan, & Carter, 2014), and the other six studies examined 12-to 13-year-old children (Barker & Maughan, 2009;Criss et al, 2009;Fatori et al, 2013;Gross et al, 2009;Hart, Atkins, & Matsuba, 2008;Karevold, Roysamb, Ystrom, & Mathiesen, 2009). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most longitudinal studies monitored young children; among these studies, five focused on the behavior of children from 6 to 7.5 years old (Anhalt, Telzrow, & Brown, 2007;Ashman, Dawson, & Panagiotides, 2008;Barker, Copeland, Maughan, Jaffee, & Uher, 2012;Campbell, Matestic, von Stauffenberg, Mohan, & Kirchner, 2007;Heberle, Krill, Briggs-Gowan, & Carter, 2014), and the other six studies examined 12-to 13-year-old children (Barker & Maughan, 2009;Criss et al, 2009;Fatori et al, 2013;Gross et al, 2009;Hart, Atkins, & Matsuba, 2008;Karevold, Roysamb, Ystrom, & Mathiesen, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Overall, however, the analyzed studies found that fewer contextual risk factors predicted fewer behavioral problems and depressive symptoms in children (Ashman et al, 2008;Barker & Maughan, 2009;Hart et al, 2008;Karevold et al, 2009;Lau et al, 2007;Lengua et al, 2008); more parental resources predicted fewer behavioral problems and psychopathologies (Allen-Meares et al, 2010;Criss et al, 2009;DuboisComtois et al, 2013;Goosby, 2007;Gross et al, 2009); more social support predicted fewer behavioral problems (Barker & Maughan, 2009;Heberle et al, 2014;Karevold et al, 2009); and greater maternal harshness correlated with more externalizing problems (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Conversely, ineffective parenting might exacerbate or worsen the effects of risk, or might present another additive risk factor. As suggested by other studies that have demonstrated the influences of environmental risk and parenting on child adjustment in children as young as 5–6 years old (Heberle, Krill, Briggs-Gowan, & Carter, 2015; Smeekens, Riksen-Walraven, & van Bakel, 2007), this may be particularly true during early developmental periods, when parents have some ability to filter and influence children’s experiences of environmental risk factors or stressful life events. Tests of parenting as a moderator are required to formally investigate this hypothesis.…”
Section: Evidence For Parenting Moderating Riskmentioning
confidence: 89%
“…Er is een aanwijzing dat sociale steun fungeert als buffer tussen stress voor de moeder, inadequaat opvoedgedrag en de ontwikkeling van internaliserend en externaliserend probleemgedrag bij het kind C (Heberle et al, 2014) 3 Er is een aanwijzing dat sociale steun de betrokkenheid van oma's een beschermende factor is tegen het ontwikkelen van externalizerende problemen, wanneer moeders een strenge opvoedstijl hanteren Barnett et al, 2010) …”
Section: Middelengebruik Tijdens De Zwangerschapunclassified